HUBUNGAN KONSUMSI GARAM BERYODIUM DAN ZAT GOITROGENIK DENGAN KEJADIAN GANGGUAN AKIBAT KEKURANGAN YODIUM (GAKY) PADA ANAK SEKOLAH DASAR TAHUN 2017 (Studi pada Anak Sekolah Dasar Negeri Terangmas di Wilayah Pertanian Kecamatan Undaan Kabupaten Kudus) - Debby Sukma Wardani; Laksmi Widajanti; Ronny Aruben (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Iodine Deficiency Disorders (IDD) is a nutritional problem due to the lack of iodine sources consumption resulting in hormonal disorders.Based on Central Java Provincial Health Office data, the coverage of eligible iodized salt in 2012 was 63.90%, in 2013 was 70.52%, in 2014 was 76.07%, in 2015 was 78.97%, and in 2016 was 81.29%. According to the result of palpation of thyroid gland examination by Undaan Integrated Service Unit in 2014, on elementary schoolchildrenwas 70.50% and in 2013 in Kudus Regency one case of IDD was found.The aim of this research is to analyze the relationship between iodized salt consumption and goitrogenic substances with the incidence of iodine deficiency disorders (IDD) in agricultural area on Terangmas elementary schoolchildren of Undaan Sub-district, Kudus Regency in 2017.The type of the research usedwas analytical research (explanatory research) with cross-sectional approach.The total number of sample were 40 samples and it usedlots sampling technique.The sample size was obtained from the total number of all students in grade 3, 4 and 5 ofthe elementary school. The data of iodine sources consumption and goitrogenic substanceswas obtained through semi-quantitative Form Food Frequency Questionnaire. The iodine content of salt was measured by using iodine test. The examination on Iodine Deficiency Disorderwas measured by palpation conducted by the nutritionist of Undaan Integrated Service Unit in Kudus Regency. The data analysis used Chi-Square test.Household salt contained 57.5%of iodine, 60%was categorized as lack of iodine source consumption, 50%was categorized as above the average of goitrogenic substances consumption in food, and 60% (24 children) suffered from IDD. There was no correlation between the iodine content of household salt and the consumption of goitrogenic substances with IDD incidence in elementary schoolchildren (p=0.747, p=0.105).There was a correlation between the iodine sources consumption in foods and the incidence of IDD in elementary schoolchildren (p=0.00). Based on the results of the research, the author suggests that parents should pay more attention to their children's food consumption, and expects to increase the knowledge about nutritious and healthy food so that they can know and give the right information.